2013
DOI: 10.1075/aral.36.2.04cam
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to communicate in english as a second language as a stable trait or context-influenced variable

Abstract: Whether Willingness to Communicate (WTC) is a permanent trait or is modified by situational context has previously been investigated in various studies (e.g. Cao & Philp, 2006; Kang, 2005; MacIntyre & Legatto, 2011). However, most research into WTC has been quantitative or conducted in the English as a Foreign Language (EFL) or Study Abroad situation in countries such as Canada, Japan, Korea and China. This article reports on the qualitative component of an exploratory mixed methods study in a New Zeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
8
19
0
Order By: Relevance
“…In Bukhari and Cheng's study (2017), which was conducted in the ESL context, on the contrary, the learners' L2 WTC was revealed to be at a high level. This is perhaps because of the significant effect of L2 learning context on an individual's WTC as pointed out by Cameron (2013). It is noteworthy that the L2 WTC level of the EFL learners was found to be moderate in all studies (Bursalı & Öz, 2017;Çetinkaya, 2005;Öz, 2014Öz et al, 2015;Şener, 2014) carried out in the Turkish EFL context.…”
Section: Is There Any Statistically Significant Difference Between Thmentioning
confidence: 93%
“…In Bukhari and Cheng's study (2017), which was conducted in the ESL context, on the contrary, the learners' L2 WTC was revealed to be at a high level. This is perhaps because of the significant effect of L2 learning context on an individual's WTC as pointed out by Cameron (2013). It is noteworthy that the L2 WTC level of the EFL learners was found to be moderate in all studies (Bursalı & Öz, 2017;Çetinkaya, 2005;Öz, 2014Öz et al, 2015;Şener, 2014) carried out in the Turkish EFL context.…”
Section: Is There Any Statistically Significant Difference Between Thmentioning
confidence: 93%
“…Fallah (2014), for example, found that teacher immediacy indirectly affected WTC through confidence and motivation. Students' WTC is also influenced by the teacher's teaching styles and classroom management (e.g., Cameron, 2013;Peng, 2012;Riasati, 2012;Zarrinabadi, 2014). For instance, Zarrinabadi (2014) suggested that students' willingness to participate in a communicative activity in class is influenced by their teacher's time given for task preparation, topic selection, and error correction.…”
Section: Classroom Atmospherementioning
confidence: 99%
“…Classroom discussions about previous language learning experiences, one-to-one interviews with the teacher, or focus groups established to discuss such topics could be beneficial. Although this study added a longitudinal dimension, combined with observations and teacher input, to a previous exploratory study (Cameron, 2013), the sample size was small and generalizability to other contexts is a problem. However, this is typical of qualitative case study research in this area (see Cao, 2013;Peng, 2011;Zhong, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The findings of a previous exploratory study (Cameron, 2013) into the WTC of Iranian participants from the same university suggested that this area of research was worthy of further in-depth investigation. Learning context was an important aspect of these participants' language learning experience, and as such led to their overall WTC (Cameron, 2013). Previous studies by Zhong (2013), Cao (2011), andPeng (2012) also support the important contribution of such contextual factors to learners' WTC.…”
Section: Context and Participantsmentioning
confidence: 99%
See 1 more Smart Citation